2018
DOI: 10.1126/scisignal.aao1520
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of human, chicken, alligator, frog, and zebrafish mineralocorticoid receptors: Allosteric influence on steroid specificity

Abstract: Although multiple steroid ligands of the glucocorticoid, mineralocorticoid, and progestin families bind to and regulate the activity of mineralocorticoid receptors (MRs), the responses to these ligands differ across species. To understand how the different domains of MRs contribute to the ligand-induced activation or inhibition of MR activity, we studied the response to eight steroids (aldosterone, 11-deoxycorticosterone, 11-deoxycortisol, cortisol, corticosterone, progesterone, 19-norprogesterone, and spirono… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 80 publications
0
74
0
Order By: Relevance
“…Because in vivo studies of binding and activation of the MR by corticosteroids and progesterone can be complicated by their binding to serum proteins [8], purified MR was needed for an accurate determination of the affinity of progesterone for human MR. Purified MR became available with the cloning of the human MR by Arriza et al, [6]. Using recombinant human MR, Arriza et al reported that aldosterone, cortisol, corticosterone, 11-deoxycorticosterone, and progesterone had a similar nM affinity for human MR. Further studies by Rupprecht et al [10], Geller et al [9] and Katsu et al [13] showed that progesterone was a human MR antagonist with sub nM affinity.…”
Section: Progesterone: An Unexpected High Affinity Antagonist For Hummentioning
confidence: 98%
“…Because in vivo studies of binding and activation of the MR by corticosteroids and progesterone can be complicated by their binding to serum proteins [8], purified MR was needed for an accurate determination of the affinity of progesterone for human MR. Purified MR became available with the cloning of the human MR by Arriza et al, [6]. Using recombinant human MR, Arriza et al reported that aldosterone, cortisol, corticosterone, 11-deoxycorticosterone, and progesterone had a similar nM affinity for human MR. Further studies by Rupprecht et al [10], Geller et al [9] and Katsu et al [13] showed that progesterone was a human MR antagonist with sub nM affinity.…”
Section: Progesterone: An Unexpected High Affinity Antagonist For Hummentioning
confidence: 98%
“…Thus, the identity of the physiological mineralocorticoid in cartilaginous fishes and ray-finned fishes is not established, although cortisol and 11-deoxycorticosterone have been proposed (39)(40)(41)(42)(43)(44)(45). Complicating the identity of the physiological mineralocorticoid in cartilaginous and rayfinned fishes is evidence that progesterone (Prog) and , along with spironolactone (Spiron) ( Figure 2), are transcriptional activators of several ray-finned fish MRs (24,36,44), including zebrafish MR (35,46), and of chicken MR (35). In contrast, these steroids are antagonists for human MR (25,27,47), alligator MR and Xenopus MR (35).…”
Section: Introductionmentioning
confidence: 99%
“…Complicating the identity of the physiological mineralocorticoid in cartilaginous and rayfinned fishes is evidence that progesterone (Prog) and , along with spironolactone (Spiron) ( Figure 2), are transcriptional activators of several ray-finned fish MRs (24,36,44), including zebrafish MR (35,46), and of chicken MR (35). In contrast, these steroids are antagonists for human MR (25,27,47), alligator MR and Xenopus MR (35). Ray-finned fish MRs and chicken MR differ in their response to Prog, 19norProg and Spiron, raising the question of whether the response to Prog and Spiron evolved in ray-finned fish before or after the divergence of ray-finned fish from the lobe-finned fish lineage that led to tetrapods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations